Enhanced vasoconstrictor potency of the fixed combination calcipotriol plus betamethasone dipropionate in an innovative aerosol foam formulation vs. other corticosteroid psoriasis treatments. (15th June 2016) - Queille‐Roussel, C.; Bang, B.; Clonier, F.; Lacour, J.‐P.
Abstract: Background: An aerosol foam formulation of fixed combination calcipotriol 50 μg/g (Cal) and betamethasone 0.5 mg/g (as dipropionate; BD) has been developed for psoriasis vulgaris treatment. Objective: To compare Cal/BD aerosol foam pharmacodynamic activity with Cal/BD ointment and with other topical corticosteroids of different potencies by assessing vasoconstrictor potential. Methods: A Phase I, single‐centre, investigator‐blinded, vehicle‐controlled, intra‐individual comparison vasoconstriction study. Healthy volunteers received a single application on selected sites of: Cal/BD aerosol foam, clobetasol propionate 0.5 mg/g cream (CP; very potent), Cal/BD ointment (potent), fluocinolone acetonide 0.25 mg/g ointment (FA; moderately potent), BD aerosol foam and aerosol foam vehicle. A seventh untreated site acted as a negative control. Skin blanching was assessed by visual (primary response criterion) and colorimetric a* and L* measurements (secondary criteria), and was analysed over time (6–32 h post‐application). Results: Thirty‐five healthy volunteers were included. All active treatments led to significantly greater skin blanching than control. By visual assessment, skin blanching with Cal/BD aerosol foam was significantly less compared with CP cream [mean AUC0–32 2560 vs. 3831; mean difference = −1272; 95% confidence interval (CI): −1598, −945; P < 0.001], similar to BD aerosol foam (mean AUC0–32 2560 vs. 2595; mean difference = −35; 95% CI: −362, 292; P = 0.83) and significantly greater than Cal/BD ointment (mean AUC0–32 2560 vs. 2008; mean difference = 552; 95% CI: 225, 878; P = 0.001) and FA ointment (mean AUC0–32 2560 vs. 1981; mean difference = 578; 95% CI: 251, 905; P < 0.001). Colorimetric assessments a* and L* also indicated significantly reduced skin blanching with Cal/BD aerosol foam compared with CP cream. No adverse events (AEs) were reported. Conclusion: Cal/BD aerosol foam can be considered a more potent formulation than Cal/BD ointment and the moderately potent FA ointment, but less potent than the very potent corticosteroid, CP cream.